1998
DOI: 10.1074/jbc.273.29.18340
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Human Homologue of theSchizosaccharomyces pombe rad17+ Checkpoint Gene

Abstract: In the fission yeast Schizosaccharomyces pombe the rad17 ؉ gene is required for both the DNA damage-dependent and the DNA replication-dependent cell cycle checkpoints. We have identified a human cDNA homologue of the S. pombe rad17 ؉ checkpoint gene, designated Hrad17. Hrad17 has 49% identity to the S. pombe rad17 ؉ sequence at the DNA level and 49% identity and 72% similarity at the amino acid level. Northern blot analysis indicates elevated levels of expression in testis and in cancer cell lines. Chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 46 publications
4
50
1
Order By: Relevance
“…hRad1, hRad9, and hHus1 Associate in a Checkpoint Complex-Comparisons of the predicted human and yeast protein sequences indicate that the human proteins are 25-30% identical and 53-57% similar to their respective homologs, with homologies extending over extensive portions of each protein (12)(13)(14)(15)(16)(17)(18). In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…hRad1, hRad9, and hHus1 Associate in a Checkpoint Complex-Comparisons of the predicted human and yeast protein sequences indicate that the human proteins are 25-30% identical and 53-57% similar to their respective homologs, with homologies extending over extensive portions of each protein (12)(13)(14)(15)(16)(17)(18). In S. pombe, spRad1 and spHus1 associate in wildtype, but not rad9, mutant yeast.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in S. cerevisiae have shown genetic and biochemical interactions among the members of the scRAD24 epistasis group (21,22), which includes S. cerevisiae homologs for HRAD1 (scRAD17), HRAD17 (scRAD24), and HRAD9 (partially homologous to scDDC1). Additionally, previous work demonstrated that hRad17 and hRad1 interacted in a two-hybrid system (16). Therefore, we addressed the possibility that hRad1 and hHus1 might interact with the checkpoint protein hRad17.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammalian counterparts of all the checkpoint rad genes except rad26 ϩ have been identified (21)(22)(23)(24)(25)(26)(27). The hRad9, hRad1, and hRad17 genes partially complement the DNA damage sensitivity of the counterpart yeast mutants (24,27,28), reinforcing the functional similarities between the human and yeast genes.…”
mentioning
confidence: 88%